Analisis Penggunaan Strategi Ungkapan Terimakasih Oleh Penutur Asli Bahasa Jepang - Arianti, Dyah Retno; Nurhayati, Silvia (IZUMI, 2019)
(Title: Analysis Of Gratitude Expresion Strategy By Japanese Native Speakers). People who learn about Japanese language generally know that gratitude expressions sayings such as "Thankyou", "I appreciate it", However, Japanese native speakers convey gratitude not only using gratitude expressions but also using other expressions. The main goal of this article is to describe strategy used by Japanese people to gratitude to other people. This research uses a quantitative descriptive approach with a questionnaire as the data source. The questionnaire write in open questionnaire type was distributed to 65 Japanese native speakers to get natural answers. The questionnaire was distributed using the random sampling method. Based on the result of questionnaire, conclude that when Japanese native speakers are gratitude to other people, Japanese native speaker mostly use the combination of two thankful strategies. When Japanese native speakers are gratitude to other people, the most used strategy is the strategy is shinteki taidou no hyoumei or expressions of psychological actions. gb777gb777slot gacorgb777gb777GB777GB777slot gacorslot gacor